GAYA KEPEMIMPINAN DEMOKRATIS UNTUK PENINGKATAN KINERJA GURU - Sodikun Sodikun (Universitas Muria Kudus, 2022)
The leadership style in his capacity as a leader will determine the success of improving the performance of teachers under his leadership. The purpose of this study was to analyze the form of using democratic leadership style to improve teacher performance at SD Negeri 1 Srobyong. This study uses a qualitative descriptive approach with a meta-analysis method. Data collection techniques by observation, interviews, tracing journals and documentation studies. The data analysis techniques in this research are data reduction, data presentation and conclusions. The results show that the democratic leadership style is seen to be more task and teacher oriented by creating a pattern of good relationships, making decisions with a deliberation system by involving their subordinates, efforts to increase teacher performance motivation, and schools are always open to receiving criticism and suggestions from their subordinates and together to find solutions to existing problems.